2014
DOI: 10.1038/gene.2014.40
|View full text |Cite
|
Sign up to set email alerts
|

Diversity in the preimmune immunoglobulin repertoire of SHR lines susceptible and resistant to end-organ injury

Abstract: We used next-generation sequencing to identify IGH genetic variation in two closely related hypertensive rat lines that differ in susceptibility to end-organ disease (SHR-A3 and SHR-B2). The two SHR lines differ extensively at the IGH locus from the rat reference genome sequence (RRGS) and from each other, creating 306 sequence unique IGH genes. Compared to IGH genes mapped in the RRGS, 98 are null gene alleles (31 are null in both SHR lines, 45 are null in SHR-A3 only, and 23 are null in SHR-B2 only). Of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 38 publications
1
21
0
Order By: Relevance
“… 55 However, there are several examples demonstrating essential functions of IGHV germline-encoded variation in antigen specificity; for example, amino acids encoded by germline IGHV1-69 alleles have been shown to make important contributions to neutralizing antibody responses against influenza, hepatitis C and Middle East Respiratory Syndrome coronavirus. 10 , 56 , 57 A recent mapping effort in rates with two disease models of differing susceptibility to spontaneous hypertension revealed that the IGH region exhibited the highest sequence divergence genome-wide between these lines, 58 consistent with the results observed here. Whether increased genetic diversity in human IGHV is associated with a dominant role of the heavy chain in antibody function remains to be seen.…”
Section: Discussionsupporting
confidence: 87%
“… 55 However, there are several examples demonstrating essential functions of IGHV germline-encoded variation in antigen specificity; for example, amino acids encoded by germline IGHV1-69 alleles have been shown to make important contributions to neutralizing antibody responses against influenza, hepatitis C and Middle East Respiratory Syndrome coronavirus. 10 , 56 , 57 A recent mapping effort in rates with two disease models of differing susceptibility to spontaneous hypertension revealed that the IGH region exhibited the highest sequence divergence genome-wide between these lines, 58 consistent with the results observed here. Whether increased genetic diversity in human IGHV is associated with a dominant role of the heavy chain in antibody function remains to be seen.…”
Section: Discussionsupporting
confidence: 87%
“…Our analysis of the whole genome sequences for the two SHR lines reveals that the IgH locus contains extensive variation between the two SHR lines, for SHR-B2 this is the most divergent region of the entire genome 20 . Variation at the IgH locus results in highly divergent serum levels of three of the four rat IgG subclasses and total serum IgG levels in SHR-A3.…”
Section: Resultsmentioning
confidence: 92%
“…Variation in the immunoglobulin heavy chain gene is very extensive and the complex, segmentally duplicated nature of this gene prevents a complete description of that variation here. In another manuscript we have completed an analysis of the variable, diversity, junctional and Fc gene segments of the IgH locus and the extensive divergence of the pre-immune immunoglobulin repertoire in these two rat lines 20 . Our findings for the other loci are summarized below and detailed in the Data Supplement.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, such IgGRdbs may be sparse or non-existent for certain species; IMGT/GENE-DB has only a single IgGRdb IGHV allele for most genes in mouse, and only a single allele for all genes in rat and rhesus macaque. Nevertheless, IGHV variation was observed in all of these species (for example, Mouse [24,25], Rat [26], Macaque [27,28]). In principle, the deep coverage of repertoire sequencing data could obviate the need for IgGRdbs by inferring the set of alleles for each subject based solely on the observed set of rearranged sequences.…”
Section: Resultsmentioning
confidence: 99%